2008
DOI: 10.1111/j.1743-6109.2007.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Giving Patients with Erectile Dysfunction the Opportunity to Try All Three Available Phosphodiesterase Type 5 Inhibitors Contributes to Better Long-Term Treatment Compliance

Abstract: Introduction There are three phosphodiesterase type 5 (PDE5) inhibitors marketed, sildenafil, Vardenafil, and tadalafil for oral treatment of erectile dysfunction (ED). Although the treatment is simple and mostly effective, around 50% has ceased to use the medication within 2 years. One recently described way to improve the compliance is to let the patient try all the three PDE5 inhibitors and to prescribe the drug(s) he and his partner desires. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 25 publications
3
38
0
1
Order By: Relevance
“…Some studies documented that PDE5i switching improved erectile function for patients who did respond to the initial PDE5i. [27][28][29][30] However, no clinical conclusion can be drawn about the use of avanafil, due to limited data.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies documented that PDE5i switching improved erectile function for patients who did respond to the initial PDE5i. [27][28][29][30] However, no clinical conclusion can be drawn about the use of avanafil, due to limited data.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy improves compliance and increases patient satisfaction. 247 Moreover, dose titration for a given PDE5 inhibitor to the maximum tolerated dose is strongly recommended because it increases efficacy and satisfaction from treatment (grade of recommendation ¼ A). 248e250 Despite the favorable clinical data, high dropout rates exist.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…A 2007 study evaluating patient compliance found that 25% of patients changed their preferred PDE5i medication over a 3-year period. 19 Reviews evaluating patient preference for filmcoated PDE5i have consistently determined that the study results are inconclusive and limited by bias.…”
Section: Patient Preferencementioning
confidence: 99%